Effect of Ulraviolet Light, pH and Temperature on the Thickening Property of Pectin Extracted from Banana, Orange and Lime Peels - K.I. Omoniyi; S. Uba; A.I. Aliyu; S. Makama (Journal of Applied Sciences and Environmental Management, 2019)
Pectin is a polysaccharide used as rheology modifier in products such as food and beverages. This work assessed the effect of UV light, pH and temperature on the thickening property of pectin extracted from banana, orange and lime peels. Pectin was extracted using alcohol precipitation method and was analyzed using FT – IR spectrometer and GCMS. pH and UV light degradation/depolymerization of pectin solutions were carried out using viscometric and statistical methods. Increase in temperature negatively affects the viscosity of the samples. The viscosity of the banana, orange and lime pectin samples decreased on exposure to UV light for both 30 and 60 days. The observed decrease in the kinematic viscosity of the samples might be attributable to depolymerization which might have occurred with the samples on exposure to the UV light. The viscosity of the samples remained the same at the pH of 4, 7 and 10. Analysis of variance (one way) indicated significant difference in the kinematic viscosity measured to determine the effect of ultraviolet light and temperature (p < 0.05). No significant difference in viscosity was observed in the effect of pH (p > 0.05). Therefore, exposure to sunlight of pectin containing food drinks can cause decline in the quality of the product.